Organization of Acenes with a Cruciform Assembly Motif - Miao, Qian; Chi, Xiaoliu; Xiao, Shengxiong; Zeis, Roswitha; Lefenfeld, Michael; Siegrist, Theo; Steigerwald, Michael L.; Nuckolls, Colin (Journal of the American Chemical Society, 2006)
This study explores the assembly in the crystalline state of a class of pentacenes that are substituted along their long edges with aromatic rings forming rigid, cruciform molecules. The crystals were grown from the gas phase, and their structures were compared with DFT-optimized geometries. Both crystallographic and computed structures show that a planar acene core is the exception rather than the rule. In the assembly of these molecules, the phenyl groups block the herringbone motif and further guide the arrangement of the acene core into higher order structures. The packing for the phenyl-substituted derivatives is dictated by close contacts between the C−H's of the pendant aromatic rings and the carbons at the fusions in the acene backbone. Using thiophene substituents instead of phenyls creates cofacially stacked acenes. In thin films, the thiophene-substituted derivative forms devices with good electrical properties: relatively high mobility, high ON/OFF ratios, and low threshold voltage for device activation. An unusual result is obtained for the decaphenyl pentacene when devices are fabricated on its crystalline surface. Although its acene cores are well isolated from each other, this material still exhibits good electrical properties.<br